Risk factors for hearing loss in neonates - Ni Luh Putu Maharani; Ekawaty Lutfia Haksari; I Wayan Dharma Artana (Indonesian Pediatric Society, 2015)
Background An estimated 6 of 1,000 children with live births suffer from permanent hearing loss at birth or the neonatal period. At least 90% of cases occur in developing countries. Hearing loss should be diagnosed as early as possible so that intervention can be done before the age of 6 months. Objective To determine risk factors for hearing loss in neonates. Methods We performed a case-control study involving 100 neonates with and without hearing loss who were born at Sanglah Hospital, Denpasar from November 2012 to February 2013. Subjects were consisted of 2 groups, those with hearing loss (case group of 50 subjects) and without hearing loss (control group of 50 subjects). The groups were matched for gender and birth weight. We assessed the following risk factors for hearing loss: severe neonatal asphyxia, hyperbilirubinemia, meningitis, history of aminoglycoside therapy, and mechanical ventilation by Chi-square analysis. The results were presented as odds ratio and its corresponding 95% confidence intervals. Results Seventy percent of neonates with hearing loss had history of aminoglycoside therapy. Multivariable analysis revealed that aminoglycoside therapy of 14 days or more was a significant risk factor for hearing loss (OR 2.7; 95%CI 1.1 to 6.8; P=0.040). There were no statistically significant associations between hearing loss and severe asphyxia, hyperbilirubinemia, meningitis, or mechanical ventilation. Conclusion Aminoglycoside therapy for >=14 days was identified as a risk factor for hearing loss in neonates.